PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR MELALUI KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Pegawai Bank BPD Jateng Cabang Pemalang) - Zeanet Ragil; Grace Tianna Solovida (Magister Manajemen STIE Bank BPD Jateng, 2020)
Organizational citizenship behavior is a personal contribution that exceeds the role demand in the workplace and is given hope by taking over the achievement of the task. The purpose of this study was to analyze the effect of transformational leadership and motivation on organizational citizenship behavior through organizational commitment as an intervening variable. The sample of this study were 51 people from a population of 51 employees. The method of determining the sample using saturated sampling. Data analysis using multiple linear regression models with two models and multiple tests. The results showed organizational commitment, transoformational leadership and motivation had a positive and significant effect on organizational citizenship behavior, transformational leadership and motivation had a positive and significant effect on organizational commitment, transformational leadership had an influence on organizational citizenship behavior through organizational commitment as an intervening variable, and motivation was absent influence on organizational citizenship behavior through organizational commitment as an intervening variable.